School Dropouts and How to Develop Them at High School Level in South Labuhan Batu Regency - Harahap, Aziddin; Gulo, Nur'ainun; Pardamean Nasution, Muda; Syahputra Harahap, Hasmi; Harahap, Arman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Dropping out of school is not one of the never-ending educational problems. This problem has taken root and is difficult to solve the cause, not only because of economic conditions, but also because of chaos in the family, and others. This is also experienced by several children in South Labuhanbatu Regency. Therefore, the author wants to know and research further about the causes of children dropping out of school. This discussion is entitled